(untitled) (Semiárida, 2024)
Germplasm banks are sites dedicated to the preservation of biological material. Its final objective is to achieve the conservation of biodiversity in the short, medium, or long term, avoiding the loss of genetic diversity caused by environmental, physical, biological factors, or as a consequence of human activities. The genetic diversity of plant species of importance for agriculture and food is conserved within the framework of different institutions, among them, the Plant Genetic Resources Network (Red-RRFF) of INTA (National Institute of Agricultural Technology) stands out. The objective of this network is to conserve and use species in a sustainable manner for different agroecological regions of the national territory. INTA has a Base Bank located in Castelar (Buenos Aires) and 21 Active Banks distributed throughout the country. Active Banks conserve in the short and medium term, collect and regenerate germplasm entries of different species. The Base Bank maintains long-term duplicates of the seed collections of the active banks. The characterization and evaluation activities allow us to know the degree of genetic diversity existing in the collections and increase the added value to them, based on knowledge about their behavior in situations of abiotic and/or biotic stress, nutritional quality, sensory evaluations, among others. Currently, progress is being made in tools for the organization and management of collections and in the application of a website that facilitates access to information on the available RRFF, in the implementation of international treaties ratified by Argentina, and fundamentally, in managing the work in common with other institutions and local communities in the search for a National Genetic Resources System.